Bridging the gaps: advancing preconception nutrition in South Asia through evidence, policy, and action - Faith Miller; Vani Sethi; Avishek Hazra; Danielle Schoenaker; Ranadip Chowdhury; Jane Hirst; Zivai Murira; Naomi M. Saville (The Lancet Regional Health - Southeast Asia)
Summary: This paper summarises the research, policy, and program gaps impeding the advancement of preconception nutrition in South Asia. In line with our evidence reviews, qualitative semi-structured interviews with researchers and programme implementers identified gaps in our understanding of the prevalence and burden of preconception malnutrition due to limited survey and programme data, poor coverage of recommended interventions, and gaps in programme knowledge on effective intervention mechanism. Key barriers identified were the lack of evidence linking preconception care with long-term maternal and child health and nutrition outcomes and how to integrate preconception nutrition interventions into national health systems. We highlight the need for evidence-based, context-specific interventions which utilise effective delivery platforms and engage appropriate actors to reach diverse groups of women and men during the preconception period. We, as part of the South Asia Preconception Nutrition Collective, present actionable recommendations to address these gaps. Funding: UNICEF Regional Office for South Asia contract number 43384734.